Effect of annual road safety publicity and enforcement campaign on road fatalities in Japan: a time series study from 1949 to 2019. Issue 2 (30th June 2021) - Inada, Haruhiko; Tomio, Jun; Nakahara, Shinji; Ichikawa, Masao
Abstract : Background: In 1948, Japan started a short-term publicity and enforcement campaign for traffic safety nationwide, and since 1952, the campaign has been conducted twice a year for 10 days. We aimed to quantify the short-term effect of the spring sessions of the campaign, which were conducted in different months in different years, on road fatalities in Japan using data from 1949 to 2019. Methods: We obtained national police data on the monthly number of road deaths and conducted a time series regression analysis with three steps: smoothing the long-term patterns with the natural cubic spline function, calculating the ratio of the monthly number of deaths to the corresponding smoothed value, and regressing the ratio on the number of months from January 1949 and the binary variable for the conduct of spring sessions. We repeated the analysis for four subperiods (1949–1964, 1965–1989, 1990–2004 and 2005–2019). Results: During the study period, there were 632577 road deaths. Our analysis revealed that the spring sessions changed the number of deaths per day by −2.5% (95% CI −4.1% to −0.9%) in the months when they were conducted. In the four subperiods, the estimated changes were −4.5% (95% CI −8.9% to −0.1%), −2.6% (95% CI −5.0% to −0.1%), −0.1% (95% CI −2.9 to 2.7) and −3.5% (95% CI −7.9 to 0.9). Conclusions: Road fatalities were reduced in the months when the spring sessions of the campaign were conducted, but the reduction was modest. The effect might have been somewhat larger until 1964, when Japan was a middle-income country.